Effect of Caliber Rolling Temperatures on Microstructure Evolution and Mechanical Properties of High‐Mn Steels. Issue 8 (14th April 2022) - Yu, WenXing; Chen, Hai Feng; Sun, ZhiLin; Fang, Wei; Feng, JianHang; Zhang, Xin; Liu, BaoXi; He, JiNing; Yin, FuXing
Abstract : Three kinds of high‐Mn steels are successfully fabricated by caliber rolling at different rolling temperatures, ranging from 773 to 1373 K. The effects of rolling temperature on the microstructure and mechanical properties of steels with different stacking fault energies (SFEs) are studied. With the increase in rolling temperature, the fibrous grains of the high‐Mn steels transform into equiaxed grains, and the microstructure evolution mechanism changes from discontinuous dynamic recrystallization to continuous dynamic recrystallization. The yield strength and microhardness of the experimental samples increase significantly with decreasing caliber rolling (CR) temperature, while the samples sacrifice various degrees of plasticity. Fe–30Mn–4Si–2Al steel with low SFE value fabricated by warm CR has the best microhardness (512 HV) and yield strength (1078.82 MPa), as well as a notable fracture elongation (11.10%) among three experimental steels. This is mainly attributed to the stability of dislocations and the dislocations and twin/ ε ‐martensite competitive mechanisms. Abstract : The Fe–30Mn–4Si–2Al steel with low stacking fault energy fabricated by warm caliber rolling has fine grains, high strength, and stable plasticity. With the increase in rolling temperature, the microstructure evolution mechanism of high‐Mn steel changes from discontinuous dynamic recrystallization to continuous dynamic recrystallization. Its yield strength gradually increases, and the dimples become deeper and larger.